EFFECTS OF WATER RESTRICTION AND EXERCISE ON HEMATOLOGICAL PARAMETERS IN BALI CALVES (Bos javanicus) FED A COMPLETE Clitoria ternatea-BASED DIET - Tanandima, Tomius; Jelantik, I Gusti Ngurah; Nikolaus, Tara Tiba (Universitas Nusa Cendana, 2025)
This study aimed to evaluate the effects of water restriction and exercise on hematological parameters in Bali calves (Bos javanicus) fed a complete diet based on Clitoria ternatea. Four post-weaning Bali calves were subjected to four treatments: T0: control (ad libitum water and feed), T1: water restriction (50% of daily water intake), T2: exercise (30 minutes 2 km daily), and T3: a combination of water restriction and exercise. The experimental design followed a Latin Square arrangement with four treatments and four periods as replication. Blood samples were collected at the end of each period to assess erythrocyte, leukocyte, hemoglobin, and haematocrite concentrations. The results showed no significant effects (P>0.05) of water restriction or exercise on any of the measured hematological parameters. Erythrocyte, leukocyte, hemoglobin, and haematocrite levels remained stable across all treatments, with haematocrite values ranging from 34.23% to 35.58%. These findings suggest that feeding Bali calves a nutritionally balanced diet containing Clitoria ternatea can help mitigate the physiological impact of environmental stressors such as water restriction and exercise. The results highlight the resilience of Bali cattle in maintaining hematological health under challenging conditions, indicating their suitability for eco-farming systems in arid and water-limited regions. Further research is recommended to explore additional physiological responses and long-term effects on animal productivity.